Pengembangan Lembaran Kerja Matematika SMP Berbasis Pendekatan Metakognisi Untuk Meningkatkan Higher Order Thinking Skill Peserta Didik - Nadia Alkhaira; Yerizon Yerizon (Jurnal Gantang, 2019)
The purpose of this study is to produce a Junior Mathematics worksheet based on metaconigration approach to improve students' HOTS with valid, practical and effective. This research is a development research using Plomp model. The results of this study are metacognition-based worksheets a) valid from the aspects of content, construct, language, and graphic, b) practical aspects of usage, time and readability, and c) effective aspects to improve the HOTS ability of students.